1998
DOI: 10.2166/nh.1998.0002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Analysis and Short-Term Forecasting of Dry Spells by Palmer Drought Severity Index

Abstract: This paper presents a non-homogeneous Markov chain approach for analyzing drought characteristics using the Palmer Drought Severity Index (PDSI). The probability mass functions of occurrence of different drought severity classes, their durations, and times of return to a particular drought class are obtained and are in turn utilized to generate the needed statistics and forecasts. Two methods of forecasting drought severity classes for one, two, and three months lead times are put forward. The methodology is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 12 publications
0
33
0
1
Order By: Relevance
“…same and have ordered categories, resulting from a pairwise comparison of dependent samples, which is the case [39]. In adjusting these models, it is assumed that the n ijk , i, j, k = 1,..., 4 are values taken by independent Poisson distributed variables and the parameter estimatorsλ,λ a i ,λ b j ,λ c k ,β, δ h andm i,j,h , h, j = 1,..., 4, obtained using the maximum likelihood method, are asymptotically normally distributed [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…same and have ordered categories, resulting from a pairwise comparison of dependent samples, which is the case [39]. In adjusting these models, it is assumed that the n ijk , i, j, k = 1,..., 4 are values taken by independent Poisson distributed variables and the parameter estimatorsλ,λ a i ,λ b j ,λ c k ,β, δ h andm i,j,h , h, j = 1,..., 4, obtained using the maximum likelihood method, are asymptotically normally distributed [50].…”
Section: Discussionmentioning
confidence: 99%
“…The methodologies include regression analysis [33], time series modeling such as ARIMA and seasonal ARIMA [34,35], artificial neural network models (ANN) [36,37] and stochastic and probability models such as Markov chains [38][39][40], log-linear models [31,41] and others [42,43]. Also, hybrid models combining two techniques have been used, for instance wavelet transforms and neural networks [44], stochastic and neural network modeling [45], wavelet and fuzzy logic models [46], adaptive neuro-fuzzy inference [47] and data mining and ANFIS techniques [48].…”
Section: Introductionmentioning
confidence: 99%
“…Markov chains [48] are commonly used to assess drought occurrence probability, and to evaluate and predict the time of occurrence of a drought event [49][50][51][52]. In this study, this method was used to examine changes in drought severity at different time scales, and to predict the occurrence probability for each degree of severity.…”
Section: Markov Chains Evaluation Methodsmentioning
confidence: 99%
“…The approach can be satisfactorily used as a predictive tool for forecasting transitions among drought severity classes up to 3 months ahead (Paulo and Pereira, 2007). An early warning system for drought management was developed using the Markov chain, in two climatic areas of Virginia, USA (Lohani and Loganathan, 1997;Lohani et al 1998). Liu et al (2009) demonstrated two advantages of the Markov chain technique for forecasting drought and rainfall conditions.…”
Section: Markov Chain Modelmentioning
confidence: 99%